2016
DOI: 10.1089/rej.2015.1712
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of High-Density Lipoprotein Cholesterol Functions by Encapsulation of Policosanol Exerts Anti-Senescence and Tissue Regeneration Effects Via Improvement of Anti-Glycation, Anti-Apoptosis, and Cholesteryl Ester Transfer Inhibition

Abstract: Consumption of policosanol (PCO), a refined mixture of sugar cane wax alcohols, can elevate serum levels of high-density lipoprotein cholesterol (HDL-C), although the molecular mechanism is still unknown. To investigate the mechanism of action responsible for the anti-senescence effects of PCO on lipoprotein metabolism and HDL functionality, we synthesized reconstituted HDL (rHDL) containing PCO. Encapsulation of PCO by rHDL (PCO-rHDL) enhanced anti-oxidant activity against cupric ion-mediated low-density lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 37 publications
9
41
0
Order By: Relevance
“…To overcome the insolubility of policosanol in aqueous isotonic buffer, we synthesized rHDL-containing PCO (PCO-rHDL). A rHDL-containing policosanol was synthesized according to our previous report [ 7 ] by the sodium cholate dialysis method using initial molar ratios of 95 : 5 : 1 for POPC : cholesterol : apoA-I containing 0.5 μ g, 2.5 μ g, or 5 μ g of policosanol.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To overcome the insolubility of policosanol in aqueous isotonic buffer, we synthesized rHDL-containing PCO (PCO-rHDL). A rHDL-containing policosanol was synthesized according to our previous report [ 7 ] by the sodium cholate dialysis method using initial molar ratios of 95 : 5 : 1 for POPC : cholesterol : apoA-I containing 0.5 μ g, 2.5 μ g, or 5 μ g of policosanol.…”
Section: Methodsmentioning
confidence: 99%
“…Policosanol enhances the beneficial functions of HDL and maximizes its antioxidant, antiglycation, and antiatherosclerotic activities along with inhibition of CETP activity [ 7 9 ]. These results suggest an association between policosanol activity and HDL functionality for enhancement of longevity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, encapsulation of policosanol into HDL was shown to enhance HDL functions and exert anti-senescence and tissue regeneration effects via improvement of anti-glycation, anti-apoptosis and CETP inhibition (11). Policosanol alone or in combination with HDL (PCO-rHDL) has been shown to potently inhibit human serum CETP activity (12).…”
Section: Introductionmentioning
confidence: 99%